PELATIHAN DIGITAL MARKETING SEBAGAI PENUNJANG KEGIATAN PROMOSI DAN PEMASARAN PADA UMKM HASIL OLAHAN LELE DI KAMPUNG LELE BOYOLALI - Asih Handayani; Sutarno (Fakultas Ekonomi Universitas Surakarta, 2024)
Abstract This Community Service Program is in collaboration with SME partners of processed catfish products located in Kampung Lele Boyolali, precisely in Mangkubumen Tegalrejo Village, Sawit District, Boyolali Regency with a distance of about 25 km from Slamet Riyadi University, Surakarta. This community service focuses more on digital marketing training to support promotion programs. This community service activity will discuss digital marketing including training in applying social media and e-commerce to promote. The results of this community service activity are able to provide convenience for catfish processed SME to expand access to marketing of SME products, besides that the enthusiasm of the participants who participated in this activity is expected to be able to improve the quality of marketing and the quantity of products sold. Because with the application of digital marketing, it can reach a wider target market, up to outside the region. Keywords: Community Service Activities; Training; Coaching; Accompaniment; Application; Digital Marketing.